Faktor-Faktor Yang Mempengaruhi Manajemen Laba Pada Perusahaan Manufaktur Di Indonesia (Jurnal Paradigma Akuntansi, 2022)
The purpose of this study is to obtain empirical evidence regarding the effect offirm's corporate strategy, leverage, independent commissioners, and audit committee onearnings management practices in manufacturing companies listed on the Indonesia StockExchange in 2017-2019. This study used 69 samples of manufacturing company data selectedthrough purposive sampling technique. This study uses secondary data in the form offinancial and annual reports from manufacturing companies listed on the Indonesia StockExchange during 2017-2019. This study uses EViews 11.0 to process data. The results of thisstudy indicate that firm's corporate strategy has a significant positive effect on earningsmanagement, while leverage, independent commissioners, and the audit committee do nothave a significant effect on earnings management.